The Persuasive Methods of ISIS in Recruiting Individuals (Scientific Approach) - abd almajeed, ahmed (ALBAHITH ALALAMI, 2019)
The rapid success and the field dilation of Daish organization in both Iraq and Syria make academic institutes and research centers to pay attention to its propaganda means to gain its public opinion, and to further investigation about new methods employed by this organization to disseminate its messages to the public, particularly young people in large areas of the world. This organization uses traditional propaganda techniques on psychological war and its levels, social network sites and platforms that are distributed online. This study seeks to expose more persuasive methods used by the organization to gain multiple classes of society and to disseminate its extremist ideological thoughts. It also studies the psychological operation and mental deception to achieve its goals and strengthens its presence on the occupied areas. This research also focuses on other Daish’s propaganda efforts comparable with the deceptive nature of such terrorist organizations, generally like propaganda of clash between the groups or different social classes, agitation of enthusiasm passion, the use of new electronic technologies of illustration to increase the psychological impact depending on the expertise and funds are obtained in different ways. The study found a number of conclusions, including: The study concludes with the following results: 1- Daish organization realizes the importance and power of media to gain public opinion, supporters and sympathizers since the beginning of its appearance representative by Abu Musab al-Zarqawi 2- Daish has additional power factors after its dilation and occupied cities in Iraq and Syria as a result of the growth of its financial resources and it polarizes new technical experts. 3-The propaganda system of Daish uses various recruit techniques and psychological operations to make youth, women and children be involved to expand its supporters by which it implement special armed operations 4- Daish has used the preachers, imams of mosques, social networking sites, info graphics, and electronic forums as a means to implicate recruits and teach them ways of belonging to this organization as well as how to make explosives via the internet. 5- It owns several propaganda arms forming the skeleton of its electronic arms including productive and audio-visual centers as well as publications like Dabiq magazine, Alshamilha magazine, and Khansa magazine. 6- Daish organization depends not only on mass communication through its new and traditional means, but also uses direct means of persuasions by training preachers and some individual practices to raise enthusiasm and passion by using the normal cassette or compact disk ( CD). 7- It uses the deceptive style and bright words to create a historical depth of its formation and show an alleged link of caliphate with the Islamic caliphate in the era of the Prophet Muhammad and his Caliphs. 8- Daish relies on persuasive techniques of psychology in order to lure young people and women, to recruit its supporters. 9- Daish shows the children, who call them cubs caliphs, in its propaganda through a series of short films. These cubs› caliphs are involved in military, field, and psychological training programs.